2019
DOI: 10.1073/pnas.1809964116
|View full text |Cite
|
Sign up to set email alerts
|

Energetic regulation of coordinated leader–follower dynamics during collective invasion of breast cancer cells

Abstract: The ability of primary tumor cells to invade into adjacent tissues, followed by the formation of local or distant metastasis, is a lethal hallmark of cancer. Recently, locomoting clusters of tumor cells have been identified in numerous cancers and associated with increased invasiveness and metastatic potential. However, how the collective behaviors of cancer cells are coordinated and their contribution to cancer invasion remain unclear. Here we show that collective invasion of breast cancer cells is regulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
145
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(164 citation statements)
references
References 47 publications
8
145
0
Order By: Relevance
“…Differential energetic dynamics during invasion have been described in breast cancer, highlighting the need to further investigate metabolic heterogeneity during collective invasion in a variety of contexts 71 . We speculate that this difference could be due to molecular heterogeneity within and between cell types, the microenvironment, and various modes of migration, all of which could influence the metabolism of invading cells.…”
Section: Discussionmentioning
confidence: 99%
“…Differential energetic dynamics during invasion have been described in breast cancer, highlighting the need to further investigate metabolic heterogeneity during collective invasion in a variety of contexts 71 . We speculate that this difference could be due to molecular heterogeneity within and between cell types, the microenvironment, and various modes of migration, all of which could influence the metabolism of invading cells.…”
Section: Discussionmentioning
confidence: 99%
“…Cell migration is an energy consuming process. 50,51 However, hypoxia/HIF signaling typically occurs alongside nutrient deprivation and metabolic challenge, which may limit energy production required for cell migration. 52 Because hypoxia/HIF challenge induced conversion to amoeboid movement with efficient single-cell speeds in low-to mid-density 3D fibrillar collagen ( Supplementary Fig.…”
Section: Amoeboid Conversion Induced By Hif Signaling Coincides With mentioning
confidence: 99%
“…suggested that the activity of leader cells was compromised. Leader cells are critical in initiating and maintaining collective invasion (Cheung et al, 2013;Zhang et al, 2019). To test whether leader cell function depends on Cx43, fluorescent mosaic spheroids of cells expressing nontargeting or Cx43 shRNA at equal ratio were allowed to invade.…”
Section: The Decreased Initiation and Prolongation Of Invasion Strandmentioning
confidence: 99%